2018
DOI: 10.1021/acssuschemeng.7b04447
|View full text |Cite
|
Sign up to set email alerts
|

Significant Acceleration of PGMs Extraction with UCST-Type Thermomorphic Ionic Liquid at Elevated Temperature

Abstract: Dependency of extraction behavior of inert platinum group metals (PGMs) like Ru­(III) and Rh­(III) on temperature has been investigated in a biphasic system consisting of HNO3(aq) and betainium bis­(trifluoromethylsulfonyl)­amide ([Hbet]­[Tf2N]) ionic liquid. The extraction reactions of Ru­(III) and Rh­(III) took 3.5 days and 113 days, respectively, at 298 K, while equilibrated within 1 and 3 h to reach 99.2% and 96.5% extraction at 353 K. Further mechanistic studies clarified that the complexation of these PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…While phosphate is not per se toxic, release of excessive amounts into aquatic environments can promote algal growth and lead to eutrophication [245] . Regarding NTf 2 − , which has been reported by many researchers referenced in this review, [142,143,145,150–152,155,157–161,163,184,185–188,195–197] its ecotoxicological potential has been established [246] …”
Section: Environmental Considerationsmentioning
confidence: 85%
“…While phosphate is not per se toxic, release of excessive amounts into aquatic environments can promote algal growth and lead to eutrophication [245] . Regarding NTf 2 − , which has been reported by many researchers referenced in this review, [142,143,145,150–152,155,157–161,163,184,185–188,195–197] its ecotoxicological potential has been established [246] …”
Section: Environmental Considerationsmentioning
confidence: 85%
“…Higher E % of Ru(III) and Rh(III) can be actually achieved using ILs as alternative non-aqueous phases. 9 , 10 , 17 , 18 However, much higher cost and difficulty in handling due to higher viscosity compared with ordinary organic solvents are main critical drawbacks of ILs in the solvent extraction. Our current work successfully demonstrated that the solvent extraction of Ru(III) and Rh(III) from HNO 3 (aq) can be facilitated even using an ordinary organic solvent like 1-octanol.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The lifetime of a hydrated H 2 O molecule in the rst coordination sphere (sH 2 O) is a measurable indicator for the lability of metal ions in the innersphere substitution reaction and sH 2 O of Rh(III) is 14 years. 36,56 This low reactivity of Rh(III) is the reason for the extremely slow extraction of Rh(III). An extraction time of more than 3 weeks was required to reach equilibrium, in the following experiments.…”
Section: Extraction Kinetics (Effect Of Contact Time)mentioning
confidence: 99%
“…Ionic liquids (ILs) have drawn interest as extractants or diluents in solvent extraction of metal ions; in particular, phosphonium-based ILs have been studied for application to PGM extraction. [30][31][32][33][34][35][36][37][38][39][40] Recently, Papaiconomou and co-workers report highly effective extraction of Rh(III) (>95%) with undiluted trihexyl(tetradecyl)phosphonium chloride ([P 66614 ][Cl]) as the extracting phase. 26,39 However, [P 66614 ][Cl] has a high viscosity (1931 mPa s at 298 K) 35 compared with those of commonly used extractant phases (i.e., a mixture of an extractant and a diluent), owing to the large and bulky cations that have long alkyl chains.…”
Section: Introductionmentioning
confidence: 99%